Can conditional transfers eradicate child marriage? - Sajeda Amin; Niaz Asadullah; Sara Hossain; Zaki Wahhaj (Institute for the Study of Labor (IZA), 2016)
Conditional cash transfers are increasingly being used by policymakers as a strategy to postpone the marriage of adolescent girls in developing countries. While this approach has met with success in the case of education and health programmes, it is unlikely, on its own, to address deeper issues related to child marriage, such as the agency of adolescent girls in their marriage decisions, sexual rights within marriage, and social norms within their own communities. We argue for a multi-dimensional, longer-term and holistic view of impact, that takes into account dimensions such as realized rights, health and access to education rather than cost-benefit based approaches that rely on single-focus indicators.
Keywords: J12; J16; Z10; 330; poverty; early marriage; South Asia; conditional transfers; cost benefit analysis